About some application of the Rademacher function (Международный научный журнал «Инженер», 2026)
The paper details the process of generalizing the classical Viyet formula expressed as infinite productsof the number using Rademacher functions. This study presents the mathematical foundations ofRademacher functions and their application to the Viyet formula, which led to various forms of thenumber expressed as infinite products. These products have not been previously identified or have beeninsufficiently investigated in previous scientific works. The approaches proposed in the paper open thepossibility of identifying new, previously unknown forms of infinite products.